Relationship between crystallographic compatibility and thermal hysteresis in Ni-rich NiTiHf and NiTiZr high temperature shape memory alloys. (December 2016) - Evirgen, A.; Karaman, I.; Santamarta, R.; Pons, J.; Hayrettin, C.; Noebe, R.D.
Abstract: The relationship between the crystallographic compatibility of austenite and martensite phases and the transformation thermal hysteresis (ΔT) of Ni-rich Ni50.3 Ti29.7 Hf20 and Ni50.3 Ti29.7 Zr20 alloys undergoing B2–B19′ martensitic transformation was studied as a function of microstructure, via differential scanning calorimetry, transmission electron microscopy, and X-ray diffraction. An experimental linear relationship of ΔT vs λ 2 (the second eigenvalue of the transformation stretch matrix) was observed for these NiTi(Hf/Zr) alloys, but with a shallower slope as compared to the universal behavior followed by alloys showing B2–B19 martensitic phase transformation. Several ternary NiTiCu and binary NiTi alloys undergoing the B2–B19′ transformation were also found to deviate from the universal behavior attributed to alloys that undergo a B2–B19 transformation, and instead, follow the trend revealed for the present alloy systems. Aged NiTi(Hf/Zr) samples, which consist of very fine nano-precipitates, followed the newly established ΔT vs λ 2 linear relationship, due to only minor changes in the microstructure. In contrast, samples with large precipitates, exhibited a large deviation from this relationship due to much more drastic changes in microstructure. Finally, despite the poor crystallographic compatibility of the austenite and martensite lattices observed in the present alloys, rationalized by large deviation of λ 2 values from 1, relatively low ΔT values were measured. This behavior is actually consistent with the newly established relationship for ΔT vs λ 2 for B2–B19′ transforming alloys, which is much less sensitive to compatibility (shallower slope). It is concluded that such a difference in the ΔT vs λ 2 slope must be a consequence of the crystallography of monoclinic martensite formation in NiTi-based alloys as long as other factors such as plasticity or major constraints to the martensitic transformation do not intervene. Graphical abstract: Image 1